Biological effects of α-radiation exposure by 241Am in Arabidopsis thaliana seedlings are determined both by dose rate and 241Am distribution. (November 2015) - Biermans, Geert; Horemans, Nele; Vanhoudt, Nathalie; Vandenhove, Hildegarde; Saenen, Eline; Van Hees, May; Wannijn, Jean; Vangronsveld, Jaco; Cuypers, Ann
Abstract: Human activity has led to an increasing amount of radionuclides in the environment and subsequently to an increased risk of exposure of the biosphere to ionising radiation. Due to their high linear energy transfer, α-emitters form a threat to biota when absorbed or integrated in living tissue. Among these, 241 Am is of major concern due to high affinity for organic matter and high specific activity. This study examines the dose-dependent biological effects of α-radiation delivered by 241 Am at the morphological, physiological and molecular level in 14-day old seedlings of Arabidopsis thaliana after hydroponic exposure for 4 or 7 days. Our results show that 241 Am has high transfer to the roots but low translocation to the shoots. In the roots, we observed a transcriptional response of reactive oxygen species scavenging and DNA repair pathways. At the physiological and morphological level this resulted in a response which evolved from redox balance control and stable biomass at low dose rates to growth reduction, reduced transfer and redox balance decline at higher dose rates. This situation was also reflected in the shoots where, despite the absence of a transcriptional response, the control of photosynthesis performance and redox balance declined with increasing dose rate. The data further suggest that the effects in both organs were initiated in the roots, where the highest dose rates occurred, ultimately affecting photosynthesis performance and carbon assimilation. Though further detailed study of nutrient balance and 241 Am localisation is necessary, it is clear that radionuclide uptake and distribution is a major parameter in the global exposure effects on plant performance and health. Highlights: Arabidopsis thaliana was exposed hydroponically to a range of 241 Am concentrations. Effects at molecular, morphological and physiological level were observed. Effects were dependent on both dose rate and 241 Am distribution.